The content validity of group guidance motivation module for secondary school students - Muhamad Arsad, Nurul Fatin; Ahmad, Jamaludin; Jailani, Othman (Faculty of Educational Studies, Universiti Putra Malaysia, 2009)
This is a descriptive design research which evaluates the content validity of a group guidance module for secondary school students. The purpose of this study is to prove that this module can really evaluate whatever data that it should (Mohd Majid Konting, 2004) and the module shows the high content validity value if it can fulfill five criteria which had been suggested by Russell in 1974. Three experts in this field were chosen to check and evaluate the module. The comments received from these experts will be used as guidance to do corrections and improve the module. This high score of the content validity proved that the module can really help the students in order to increase students' inner motivation as well as to be successful students just like the objectives stated.